THE LONGITUDINAL AND TORSIONAL OSCILLATIONS OF A ROD SYSTEMS WITH TREE-LIKE OR ANNULAR STRUCTURE - Raspopov, O. S. (Science and Transport Progress, 2008)
The methods based on the theory of graphs and automatic machines are applied to research of longitudinal and rotational vibrations of rod constructions with tree or ring structure. High efficiency of the topological analysis of the graphs representing such systems is shown, the tables of transition for determination of codes of boundary parameters of rods are made, the technique of drawing up frequency equations in the vector-matrix form is presented.